Mathematical Problem Solving Through Mobile Learning Development Based on Assemblr Edu - Mahendra Halim, Ilham; Susilawati, Wati; Sugilar, Hamdan (KnE Social Sciences, 2024)
Assemblr EDU based on mobile learning as a learning resource can be accessed anytime and anywhere. However, the utilization of these learning resources has not been optimal, so it has an impact on the quality of mathematical problem–solving abilities that need to be improved. The purpose of this research is the development of teaching materials through mobile learning based on EDU Assemblr. The method used is the development of the ADDIE model. Collecting data through observation techniques, interviews, studies from linguists, media design experts, content experts, tests, and questionnaires. The implementation phase of the trial has been carried out on students of class XI MIPA 7 State Senior High School in Bandung, Indonesia. In data analysis, the problem–solving ability test was analyzed quantitatively, and the questionnaire was analyzed qualitatively. The development of mobile learning based on Assemblr EDU received proper criteria from experts. The level of effectiveness and practicality of teaching material products is categorized as sufficient, so that it gets a good attitude from teachers and students. The development of mobile learning based on EDU assemblr as a learning resource facilitates the process of concept construction, interaction, and reflection so that there is an increase in students’ mathematical problem-solving abilities. Keywords: mathematical, problem solving, mobile learning, assemblr edu